Serotypes Of E. Coli From Various Fish And Ready-To-Eat (Rte) Fish Food Products - Gupta, Bhavana; Ghatak , Sandeep; Gill , J.P.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A study was conducted for evaluation of major serotypes of E. coli from various fish and Ready To-Eat (RTE) fish food products. A total of 184 samples comprising 96 raw fish and 88 ready- to eat (RTE) fish products were collected from Ludhiana and other parts of Punjab and were subjected to test for E. coli employing suitable microbiological methods. All the isolates of E. coli were typed for ’O’ antigen. Results of serotyping revealed a total of 15 different serotypes among the E. coli isolates. More variation was observed among isolates from raw fish samples (12 serotypes) while RTE fish products harboured only 5 different serotypes.